Luminescence chronology for identifying depositional sequences in an uplifted coast since the Middle Pleistocene, eastern Japan - Tamura, T.; Okazaki, H.; Naya, T.; Nakashima, R.; Nakazato, H.; Seike, K.; Okuno, J. (Frontiers in Earth Science, 2022)
Feldspar post-infrared infrared stimulated luminescence (pIRIR) dating is an advantageous trapped-charge dating method concerning late Quaternary sedimentary records for its direct applicability to clastic sediments and wide time coverage. Its application to depositional sequences in various coastal settings potentially improve our understanding of long-term sea-level changes and regional tectonics that the sequences record. The Kanto coastal plain, eastern Japan is situated in a unique tectonic setting near the triple junction of plate boundaries and characterized by extensive development of the Last Interglacial raised marine terrace in contrast to the longer-term subsidence trend. In this article, we document the application of feldspar pIRIR dating to a 35-m-long sediment core collected from the marine terrace in the northeastern Kanto plain and examine how effective its chronology is for identifying depositional sequences related to the relative sea-level fluctuations since the Middle Pleistocene. The sediment core shows a succession of seven facies units, A to G, in ascending order, representing the shallow marine to shelf (units A to C), fluvial to brackish salt marsh (unit D), beach to shoreface (unit E), fluvial to aeolian (unit F), and loess (unit G) sedimentation. According to pre-tests, pIRIR at 225°C after prior infrared stimulated luminescence at 50°C (pIRIR225) was chosen as an optimal signal for dating. pIRIR225 is characterized by modest anomalous fading with an average g2days-value of 1.8%/decade. Fading-corrected pIRIR225 ages are consistent with the stratigraphy. Units A and B are dated as Marine Oxygen Isotope Stage (MIS) 7 and units C to F as MIS 5. However, uncertainties of individual age estimates do not allow further chronological correlation. Instead, using sea-level changes inferred from characteristic facies transitions as additional constraints, units C to F can be correlated to sub-stages in MIS 5. Unit E represents coastal progradation during the MIS 5c sea-level highstand, which refines the date of the marine terrace around the core site as MIS 5c and revises up the rate of the tectonic uplift accordingly. Our results exemplify a successful application of feldspar pIRIR dating for identifying depositional sequences formed in relations to 100-kyr glacial cycles, in which, with additional information of the sedimentary facies, higher-frequency sequences may be defined.